2015
DOI: 10.1039/c4tc02766c
|View full text |Cite
|
Sign up to set email alerts
|

Fluorene co-polymers with high efficiency deep-blue electroluminescence

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full DRO policy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 38 publications
5
12
0
Order By: Relevance
“…The polymers are deep blue / violet emitters (λ max PL in thin films: 421 and 401 nm, respectively). They exhibit very little solvatochromism, in agreement with previous work on fluorene co-polymers; 29,30,32 the small changes observed can be explained by the different refractive index of the solvents. From the photophysical data in Table 2 it can be observed that both CF1 and CF2 emissions peak at ca.…”
Section: Optical Propertiessupporting
confidence: 89%
See 1 more Smart Citation
“…The polymers are deep blue / violet emitters (λ max PL in thin films: 421 and 401 nm, respectively). They exhibit very little solvatochromism, in agreement with previous work on fluorene co-polymers; 29,30,32 the small changes observed can be explained by the different refractive index of the solvents. From the photophysical data in Table 2 it can be observed that both CF1 and CF2 emissions peak at ca.…”
Section: Optical Propertiessupporting
confidence: 89%
“…29,30,31 In an alternative approach, 9,9diphenylfluorene units serve to disrupt conjugation in the polymer backbone leading to PLEDs with EQE values of η ext, max 3.9%, L max of 274 cd m -2 with CIE xy coordinates (0.17, 0.07). 32 It is also established that meta-linked aromatic units in the backbone can blue shift emission by reducing the effective conjugation length. 33,34,35 Very preliminary electroluminescence data showed blue emission (EQE 1.32%; CIE xy 0.16; 0.11).…”
Section: Introductionmentioning
confidence: 99%
“…In compounds based on D–A systems, fluorenes and their derivatives are broadly used as electron donors, and quinolines,17 benzotriazoles,18,19 arylimides,20 and cyanoacetic acid21 functions are used as acceptor moieties. Fluorenes, polyfluorenes, and their derivatives show potential in optoelectronics and photonics as blue light emitters and are used widely in OLEDs,22 as hosts in green and sky blue phosphorescent OLEDs (PhOLEDs),2326 in solar cells (SCs),27 and in FETs 28. However, fluorene derivatives exhibit lower power efficiencies or excited‐state lifetimes compared with those of polymeric green and red emitters, for instance; however, on the other hand, they possess excellent chemical and thermal stabilities, good solubilities, electron‐transport properties, and reasonably high fluorescence quantum yields 29,30.…”
Section: Introductionmentioning
confidence: 99%
“…Adopting weak conjugate structure in polymer backbone is also a good strategy to realize deep‐blue emission. The carbazole‐alt‐fluorene copolymers with CIE coordinates of (0.16, 0.08) and the poly(fluorenes‐co‐9,9‐diphenylfluorene)s with CIE coordinates of (0.16, 0.07) were prepared by meta‐linked carbazole unit in the backbone and by 9,9‐diphenylfluorene to disrupt backbone π‐conjugation, respectively …”
Section: Introductionmentioning
confidence: 99%